Journal of Creative Communications (New Delhi Sage Publications)
The Journal of Creative Communications (JOCC) promotes inquiry into Contemporary communication issues within wider social, economic, cultural, technological and management contexts, and provides a forum for the discussion of theoretical and practical insights emerging from such inquiry. JOCC is a double blind peer reviewed journal.
Keywords: Artificial Intelliegnce; Social Network Expansion; Media